The limits of personal experience - Ganuthula, Venkat Ram Reddy (Frontiers in Psychology, 2024)
This article examines how three types of experience-personal, related others, and unrelated others-influence decision-making. We present the complexities and nuances in using these experiential sources to suggest that personal experience is preferred to the other two sources. We discuss the implications of this preference for decision-making processes, especially in contexts involving transformative outcomes. To conclude, we discuss how people rely on other experiential sources when their preferred source is limited.